ANALISIS DAYA TARIK WISATA DAN PROMOSI TERHADAP MINAT KUNJUNGAN WISATAWAN DI MUSEUM KAYU TUAH HIMBA KABUPATEN KUTAI KARTANEGARA - Ariansyah Ariansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine whether or not the influence of interest visiting factors, namely tourist attraction and promotion, on the interest of tourist visits to the Kayu tuah himba Kutai Kartanegara museum. The subjects in this study were tourists who came or had visited the Kayu Tuah Himba Museun, with a total sampling of 100 respondents. The results of this study indicate if there is an influence between attractiveness and interest in tourist visits at the KTH Museum, Kutai Kartanegara Regency with a standardized regression value of 0.734. The t test results show t count 8.920 with a significance value of 0.000 using the confidence level α = 95% (0.05). Then other results found that there is no influence between promotion and interest in visiting is explained by the value of the promotion variable coefficient from the standardized regression equation of (0.098). The t test results show t count (1.189) with a significance value of 0, 237. By using α = 95% (0.05). And then the results of all variables when tested together get the results. Based on the F test, it is obtained that F count is 45.131 with a significance level of 0.000. Therefore the probability is much smaller than (0.000 <0.05) and F count is greater than F table (45.131> 3.09) which means that there is a significant influence between attractiveness and promotion on interest in visits, with the coefficient results. shows a figure of 0.471 which can be interpreted if the attractiveness and promotion variables contribute 47.1% to the interest of tourist visits at the KTH Museum, Kutai Kartanegara Regency and the remaining 52.9% of the contribution is given by variables or other factors outside of this study.